Bella goes to the sea - Blathwayt, Benedict (London : Red Fox, 2000)
William the fisherman is very cross when Bella follows his boat out of the sea - but how lcuky for him that she does!
Keywords: Goose -- Fiction; Fisherman -- Fiction